Konstruksi Filsafat Pendidikan Islam Profetik-Heuristik - Shulhan (AN NUR: Jurnal Studi Islam, 2015)
Islamic education ontologically is a structured effort, sustained for making human capable of science, ethical and responsible and has a good work ethic sourced the Qur’an and Hadith. The Islamic education Focus is the transfer of knowledge that can touch the human reality of the real and the abstract form of heart, spiritual and physical as well as human possible touching parts in the form of potential. Source of acquiring knowledge are the senses, reason and intuition so that developing learning rational, empirical and intuitive- religious. With these media can be validated science correctly. The purpose of education in Islam (axiological) is formed and aesthetic values that are empirical, rational and intuitive- religiosity. With humans Islamic education are expected to have good character, morals karimah, broad knowledge and a high work ethic and responsible.